Developing English Materials for Military Cadets - Puspitasari, N.N.S.W. (Universitas Pendidikan Ganesha, 2018)
This research was intended to find out the topics needed, develop new materials, and investigate the quality of the developed English materials for Military Cadets which will be used at Rindam IX Udayana, one of military base camps in Bali. The existing books used were lack of some aspects; layout and design and grammar points. As it answered those purposes mentioned previously, the design of this research was Research and Development proposed by Hannafin and Peck. The subjects of this research were soldiers and the object was the design of course materials. The procedures of developing the product were (1) Need Assessment-evaluation and revision, (2) Design-evaluation and revision and (3) Development/Implementation-evaluation and revision. Based on the procedures being followed, it is found that the subjects needed ten topics namely greeting, introduction, communicating by phone, sports and fitness, requesting and commanding, asking and giving help, surviving by enough supply, giving briefing in war games, asking for and giving direction, and taking transportations. Further, the quality of the developed textbook is good; this was proven by expert judges. In addition, the findings of this research are useful for military cadets, instructor, and institution itself.